Gold nanorods functionalized by a glutathione response near-infrared fluorescent probe as a promising nanoplatform for fluorescence imaging guided precision therapy. Issue 25 (17th June 2019) - Huang, Yan; Liu, Qingluan; Wang, Yunqing; He, Na; Zhao, Rongfang; Choo, Jaebum; Chen, Lingxin
Abstract : The AuNR-based nanoplatform integrated the functions of the glutathione response fluorescent probe and phototherapy. Abstract : Theranostics nanoplatforms offer opportunities for imaging-guided precision therapy and hold great potential for clinical applications. In most reported works, the imaging unit has a lack of site selectivity, and is always kept in the "on" modality regardless of whether it is in normal tissues or tumor sites, increasing the risk of unsafe treatment. Herein, we designed a near-infrared (NIR) fluorescence-guided theranostics nanoplatform by integrating the functions of tumor-response and photodynamic therapy (PDT)/photothermal therapy (PTT). A novel NIR fluorescent dye, CyPT, with excellent optical and PDT/PTT properties, was synthesized and linked onto the gold nanorods (AuNRs) to form CyPT–AuNRs nanohybrids via a sulfur–sulfur bond that can be broken by glutathione (GSH) with high selectivity and sensitivity. In normal cells where the concentration of GSH is low, the fluorescence of CyPT is quenched by the AuNRs. By contrast, the high level of GSH in tumor cells leads to the breaking of the sulfur–sulfur bond, resulting in the release of CyPT and the accomplishment of a "off–on" fluorescence response. Followed by precise NIR tumor-imaging diagnosis, the PDT and PTT treatment which rely on the released CyPT and AuNRs, respectively, can be effectively performed. The CyPT–AuNRs nanoplatform has been successfully applied to the treatment of tumor xenograft models and no distinct damage has been observed in the nearby normal tissues. This versatile nanoplatform has potential for use in targeted tumor imaging and precision therapy.